2007
DOI: 10.1002/nav.20214
|View full text |Cite
|
Sign up to set email alerts
|

Combining standardized time series area and Cramér–von Mises variance estimators

Abstract: Abstract:We propose three related estimators for the variance parameter arising from a steady-state simulation process. All are based on combinations of standardized-time-series area and Cramér-von Mises (CvM) estimators. The first is a straightforward linear combination of the area and CvM estimators; the second resembles a Durbin-Watson statistic; and the third is related to a jackknifed version of the first. The main derivations yield analytical expressions for the bias and variance of the new estimators. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…and the result (13) follows by Equations (23) We know from [11] that for the MA(1), the following expectation holds exactly:…”
Section: Proof Of Theoremmentioning
confidence: 97%
See 3 more Smart Citations
“…and the result (13) follows by Equations (23) We know from [11] that for the MA(1), the following expectation holds exactly:…”
Section: Proof Of Theoremmentioning
confidence: 97%
“…Now we will derive Var( D J,r (n)) for the MA (1) by calculating the components of Equation (27). First, we know from [11] that for the MA(1),…”
Section: Proof Of Theoremmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be shown that the DW estimator has relatively low variance but suffers from high small-sample bias (Goldsman et al, 2007). To overcome this bias problem at only a modest cost in variance, Batur et al (2009) define the modified jackknifed DW estimator from the jth overlapping batch,…”
Section: Overlapping Modified Jackknifed Durbin-watson Estimatormentioning
confidence: 99%